Cholera disease in iraq and the invetigation of some virulence of vibrio locally isolated from diarrhea case (Baghdad Science Journal, 2005)
A survey statistician for cholera in Iraq for 1980 and until 2003 show that cholera is endemic in Iraq and that the highest number of casualties recorded in the years 1998-1999 and increasing spread of the disease during the wars in hot climates, wet a study bacteriological used where circles selective and tests Alkouhaoah examinations serological system